Baseline Prevalence of Trachoma in Refugee Settlements in Uganda: Results of 11 Population-based Surveys. - Baayenda, Gilbert; Mugume, Francis; Mubangizi, Alfred; Turyaguma, Patrick; Tukahebwa, Edridah M; Byakika, Sarah; Kahwa, Binta; Kusasira, Darlson; Bakhtiari, Ana; Boyd, Sarah; Butcher, Robert; Solomon, Anthony W; et al. (Ophthalmic Epidemiology, 2023)
There are several settlements in the Northern and Western Regions of Uganda serving refugees from South Sudan and Democratic Republic of Congo (DRC), respectively. Trachoma prevalence surveys were conducted in a number of those settlements with the aim of determining whether interventions for trachoma are required. An evaluation unit (EU) was defined as all refugee settlements in one district. Cross-sectional population-based trachoma prevalence survey methodologies designed to adhere to World Health Organization recommendations were deployed in 11 EUs to assess prevalence of trachomatous inflammation-follicular (TF) in 1-9-year-olds and trachomatous trichiasis (TT) unknown to the health system in ≥15-year-olds. Household-level water, sanitation and hygiene coverage was also assessed in study populations. A total of 40,892 people were examined across 11 EUs between 2018 and 2020. The prevalence of TF in 1-9-year-olds was <5% in all EUs surveyed. The prevalence of trachomatous trichiasis (TT) unknown to the health system in ≥15-year-olds was <0.2% in 5 out of 11 EUs surveyed and ≥0.2% in the remaining 6 EUs. A high proportion of households had improved water sources, but a low proportion had improved latrines or quickly (within a 30-minute return journey) accessible water sources. Implementation of the antibiotic, facial cleanliness and environmental improvement components of the SAFE strategy is not needed for the purposes of trachoma's elimination as a public health problem in these refugee settlements; however, intervention with TT surgery is needed in six EUs. Since instability continues to drive displacement of people from South Sudan and DRC into Uganda, there is likely to be a high rate of new arrivals to the settlements over the coming years. These populations may therefore have trachoma surveillance needs that are distinct from the surrounding non-refugee communities. Implementation of the antibiotic, facial cleanliness and environmental improvement components of the SAFE strategy is not needed for the purposes of trachoma's elimination as a public health problem in these refugee settlements; however, intervention with TT surgery is needed in six EUs. Since instability continues to drive displacement of people from South Sudan and DRC into Uganda, there is likely to be a high rate of new arrivals to the settlements over the coming years. These populations may therefore have trachoma surveillance needs that are distinct from the surrounding non-refugee communities.
Keywords: Trachoma; Uganda; neglected tropical diseases; prevalence; refugee